Spatial restructuring and development characteristics of villages and the revitalization path: a case study of the X County of Zhejiang Province in China - Zhang, Shuifeng; Chen, Yaxi; Zhang, Xin (Frontiers in Sustainable Cities, 2024)
Rural development and restructuring are critical steps towards achieving optimal spatial adjustment for regional and rural revitalization. Using the rural regional system and the TOPSIS model supported by the entropy value method, this study analyzed the model of rural development and spatial restructuring in the study area from 2000 to 2020 The study examined the exchange and change and discussed the internal logical correlation and role relation among them. The results indicated that:(1) During the study period, the level of rural development in the study area increased considerably. The rural regional function shifted from a lower level of homogenous development to a higher level of diversified development, which are important features of the evolution of economic and social development levels.(2) Spatial restructuring was characterized by temporal continuity and non-linearity of stages. The overall shape transformed from "dispersionhomogeneity-differentiation."(3)The coupling coordination degree of the two subsystems showed a constant rise to a low level, with apparent temporal heterogeneity. The type of coupling coordination became a benign optimizing direction with a significant level of heterogeneity. Rural revitalization depends on the coupling and coordination among economic, social, ecological, and spatial systems. The research results provide baseline information to decipher the path of rural revitalization at various degrees of coupling and promoting sustainable rural development.